مدى تبني المؤسسات غير الربحية مفهوم التسويق بالعلاقات (من وجهة نظر العاملين في هذه المؤسسات) - سويدان, نظام موسى; طمليه, إلهام فخري (Latakia University Journal - Economic and Legal Sciences Series, 2019)
هدفت الدراسة إلى التعرف على مدى تطبيق وتبني المؤسسات غير الربحية العاملة في مدينة عمان لمفهوم التسويق بالعلاقات باعتباره مدخلا لتقوية العلاقات طويلة الامد مع المستفيدين من خدماتها والمانحين والداعمين لانشتطتها. تم توزيع (300) استبانه على موظفي (10) مؤسسات غير ربحية ، حيث تم استرداد (157) استبانه خضعت للمعالجة الاحصائية باستخدام برنامج SPSS ، تم احتساب اختبار صدق وثبات البيانات (كرونباخ الفا ) حيث بلغت قيمته 93.37 %. كما تم احتساب المتوسطات الحسابية للأسئلة التي تضمنتها أداة القياس، بالاضافة لاختبار ( t ) لاختبار الفرضية الرئيسة والفرضيات الفرعية المنبثقة عنها، واختبارANOVA لاختبار الفرضية الرئيسة الثانية والفرضيات الفرعية الخاصة بها. وخلصت الدراسة إلى أن المؤسسات غير الربحية الأردنية تتبنى وتطبق مفهوم التسويق بالعلاقات ضمن سياساتها العملية من حيث جذب الزبائن، والتعرف على حاجاتهم، و برامج الاحتفاظ بهم، وتعزيز ودعم ولائهم. This study aims at examining to what extent nonprofit institutions, in Amman, apply relationship marketing concept, as a marketing approach to strengthening long-term relations with the beneficiaries, donators and sponsors of their activities. The study, also, attempted to investigate whether demographic variables contribute to the application of relationship marketing in those institutions. To achieve these objectives, (300) questionnaires were distributed to the employees of ten nonprofit institutions working in Amman, (157) of these questionnaires were studied and handled statistically, by using SPSS program. The study came up with the following findings: the nonprofit institutions apply relationship marketing concept, which includes: prospecting, satisfying, retaining, and enhancing customers’ loyalty. There is no significant effect of the demographic variables (except for the experience of the employee).